If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 7 + -8 = 0 Reorder the terms: 7 + -8 + 3m = 0 Combine like terms: 7 + -8 = -1 -1 + 3m = 0 Solving -1 + 3m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3m = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 3m = 0 + 1 3m = 0 + 1 Combine like terms: 0 + 1 = 1 3m = 1 Divide each side by '3'. m = 0.3333333333 Simplifying m = 0.3333333333
| 5z-7-2z+4=0 | | 10x-36=-2x-20 | | 5x+73=11x+12 | | x^3-2x-21=0 | | 7(2n-5)=(9n+5)+1 | | 11+5(2-x)=-3(x-3) | | V=3.14*2h | | -12=9x-6(2x+5) | | 9*(5*x-50)=0 | | A=4*3.14r | | 1/5*(-10)-2 | | 2x+1+6x=73 | | A=1/2(b+c) | | 35=-3x+13x-62 | | -4-2x=-26 | | 57=3x+6x+3 | | Y+6/5=Y+8/7 | | 1-0.4k=1 | | -6.4=-2.5tx | | 5a+2b=30 | | X-5*(-2)=-1 | | a-5=-24 | | -3+3=5s+21 | | -2a+21+6a=4a-7a | | 2*6=14-y | | ax+b=cx+2 | | 2x=14-(-2) | | 10x-19x=6x+1 | | 8+x/9=7 | | 4x-5x+20=-2 | | (x^2-3x+2)x=2184 | | -2x-2x=35-7 |